Enhancing English Vocabulary Mastery Through Sing-Along Teaching Technique At 11th Grade Of Ma Mu’min Cendekia Babelan - Aisah Ekarani (Syntax Literate, 2022)
This research is aimed to prove that English songs can be used as interesting tools to teach English, especially for enhancing the teaching vocabulary. As mentioned by Rahayu, D. (2022), since the students can make vocabulary study enjoyable or challenging for students, English songs are regarded as an excellent and entertaining technique to teach. Besides, song lyrics consist of simple daily words. Teaching English using singing songs can be used as an alternative tool because students learn those words unconsciously. The study was about enhancing students' vocabulary through a sing-along teaching technique. The subject of the study was eleventh-grade students of MA Mu'min Cendekia Babelan, Academic Year 2021/2022 which consisted of 23 students. This study aimed to increase students' vocabulary through the sing-along teaching technique. The method of this research was qualitative research and the object was to teach vocabulary through the sing-along method. This was classroom action research which consisted of two cycles. In collecting the data, the researchers used a pre-test, observation sheet, and post-test. The result of this research showed that the use of the sing-along teaching technique succeeded in improving students' vocabulary. It can be seen from the result of the research showed that there was an improvement from Cycle I to Cycle II in the student's participation in the introduction, discussion and practice. In the students' achievement, Cycle I was 72.78, and the average score of the Cycle II was 83.73. It was a good category. So, it can be concluded that songs have a significant impact on improving students' vocabulary.